Concentração de sais da soluçtiao avaliada pela condutividade elétrica na zona radicular do crisântema sob irrigação por gotejamento - Mota, Poliana Rocha D'Almeida [UNESP]; Villas Boas, Roberto Lyra [UNESP]; de Sousa, Valdemício Ferreira (My University, 2006)
The effects of salt concentration levels in electrical conductivity (EC) were evaluated in chrysanthemum root, cultivated in substrate using two sampling methods, under greenhouse conditions. The experiment was carried out in Paranapanema, São Paulo using the experimental design in randomized blocks and four replications. The treatments consisted of eight sampling periods of substrate solutions in pots: 7, 14, 21, 28, 35, 42, 49 and 56 days after strike root and five salt concentration levels of applied saline solution: 1.42; 1.65; 1.89; 2.13 and 2.36 dS m -1 in the vegetative period and during the reproduction period of flower budding: 1.71; 1.97; 2.28; 2.57 and 2.85 dS m -1. The substrate solution EC monitoring was done using two methods: solution extractors and 1:2 water diluted solution. The use of solution extractors and 1:2 water diluted solution allowed substrate solution EC monitoring along the culture cycle; the amount of salt concentration applied in the substrate caused the substrate salinity increase; the method using solution extractors presented higher EC values in the substrate.
Salt oncentration in solution evaluated by the electrical conductivity in chrysanthemum root zone under trickle irrigation
Keywords: Dendranthema grandiflora; Salinity; Solution extractor; Electric conductivity; Irrigation; Plants (botany); Salts; Sampling; Separators; electrical conductivity; experimental design; irrigation; salinity; Chrysanthemum; Chrysanthemum x morifolium